2021
DOI: 10.1021/acs.est.1c04679
|View full text |Cite
|
Sign up to set email alerts
|

Full Characterization of the UV Hydrodebromination Products of the Current-Use Brominated Flame Retardants Hexabromobenzene, Pentabromotoluene, and Pentabromoethylbenzene

Abstract: UV transformation was studied with three structurally closely related current-use brominated flame retardants (cuBFRs), i.e., hexabromobenzene (HBB), pentabromotoluene (PBT), and pentabromoethylbenzene (PBEB). Irradiation in toluene and benzotrifluoride (BTF) showed pseudo-first-order kinetics. Repeated high-performance liquid chromatographic (HPLC) fractionation, available reference standards, dedicated syntheses, gas chromatography with mass spectrometry (GC/MS), GC separation on two different phases includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…PBBz, TeBBz, and TrBBz were reported to be the step-by-step debromination products of HBBz under abiotic/biotic degradation/metabolism conditions. 13 , 49 , 50 No significant correlation was found between the concentrations of PBBz/TeBBz/TrBBz and HBBz in either porpoise or dolphin blubber samples, suggesting that the source of TrBBz/TeBBz/PBBz and HBBz is different in the investigated samples, and the debromination of HBBz may not be the main source of PBBz, TeBBz, and TrBBz in the investigated marine mammals. PBBz is widely used in polymeric materials, electronic equipment, and household furniture and has become ubiquitous in the aquatic environment and biota owing to relatively high bioaccumulation potential, while reports on the direct production and use of TrBBz and TeBBz are lacking.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…PBBz, TeBBz, and TrBBz were reported to be the step-by-step debromination products of HBBz under abiotic/biotic degradation/metabolism conditions. 13 , 49 , 50 No significant correlation was found between the concentrations of PBBz/TeBBz/TrBBz and HBBz in either porpoise or dolphin blubber samples, suggesting that the source of TrBBz/TeBBz/PBBz and HBBz is different in the investigated samples, and the debromination of HBBz may not be the main source of PBBz, TeBBz, and TrBBz in the investigated marine mammals. PBBz is widely used in polymeric materials, electronic equipment, and household furniture and has become ubiquitous in the aquatic environment and biota owing to relatively high bioaccumulation potential, while reports on the direct production and use of TrBBz and TeBBz are lacking.…”
Section: Resultsmentioning
confidence: 83%
“…Combined with HBBz quantified via target analysis, in total, four bromobenzenes were found in the cetacean bubbler samples in this study. PBBz, TeBBz, and TrBBz were reported to be the step-by-step debromination products of HBBz under abiotic/biotic degradation/metabolism conditions. ,, No significant correlation was found between the concentrations of PBBz/TeBBz/TrBBz and HBBz in either porpoise or dolphin blubber samples, suggesting that the source of TrBBz/TeBBz/PBBz and HBBz is different in the investigated samples, and the debromination of HBBz may not be the main source of PBBz, TeBBz, and TrBBz in the investigated marine mammals. PBBz is widely used in polymeric materials, electronic equipment, and household furniture and has become ubiquitous in the aquatic environment and biota owing to relatively high bioaccumulation potential, while reports on the direct production and use of TrBBz and TeBBz are lacking. ,, The developed industry and high population density of the PRD may promote the wide production and use of PBBz, and the presence of PBBz in marine mammals can mainly be attributed to the direct emission from the PRD rather the degradation/debromination of HBBz.…”
Section: Resultsmentioning
confidence: 85%
“…Photodegradation has more efficient performance compared with microbial degradation with slow degradation rate [ 20 , 21 ]. At present, some researchers have conducted preliminary studies on the photodegradation of NBFRs, mainly from two aspects: on the one hand, the effects of experimental conditions, including light conditions, environmental media [ 22 , 23 ] and the degradation kinetics of NBFRs [ 24 , 25 ]; on the other hand, the degradation pathway and degradation mechanism of NBFRs [ 26 , 27 ]. It can be found that organic solvents can be used to simulate the composition of environmental media [ 28 ], and research on the transformation of NBFRs in different polar solvents is conducive to analyzing their degradation characteristics in the actual environment.…”
Section: Introductionmentioning
confidence: 99%